Beyond Automation: Opportunities and Limitations of ChatGPT in English Language Learning - Widya Intan Handayani; Lucky Rahayu Nurjamin (Ma'soem University, 2026)
This study examines the integration of ChatGPT in English language learning, focusing on both its opportunities and challenges. Using a qualitative approach, the research explores the experiences of college students in the Priangan Timur of West Java, Indonesia, who use ChatGPT to support their English learning. Data were collected through semi-structured interviews with three students. The findings show that ChatGPT offers several advantages, including instant feedback, adaptive learning tailored to individual proficiency levels, and flexible access to learning anytime and anywhere. Participants also expressed optimism regarding the future development of ChatGPT, particularly its potential to provide more personalized, interactive, and context-aware learning experiences. However, the study also identifies several challenges, including ChatGPT’s limited capacity to provide in-depth explanations, its inability to fully replace human interaction and emotional engagement, and concerns related to data privacy and security. The study concludes that ChatGPT should be viewed as a complementary tool rather than a replacement for traditional learning, with human educators remaining essential for developing learners’ contextual understanding and communicative competence. These findings highlight the importance of ongoing development in ChatGPT technologies to support more authentic and ethical language learning experiences.